Representations of the Belt and Road Initiative : A Transitivity Analysis of the News Coverage of China Daily - Aunesluoma, Mari (My University, 2024)
The Belt and Road Initiative (BRI) was announced in 2013 as a new central feature of the People’s Republic of China’s foreign policy. Since then, it has been the subject of numerous studies from various perspectives but how it has been represented in China’s English-language media has not been widely studied. To remedy this, this study sought to answer two research questions: (1) how was the BRI represented in the coverage of China Daily, the biggest English-language broadsheet newspaper in the PRC, and (2) did the representations of the BRI change between 2017 and 2019, when the first and second Belt and Road Forums for International Cooperation, which brought a spotlight on the BRI, were held. These questions were answered through examining a corpus of news articles collected from China Daily by performing a Transitivity analysis based on M.A.K. Halliday’s Systemic Functional Grammar. In addition, the thesis utilized a Critical Discourse Analysis approach, which was adopted due to the oppressive structure of the Chinese media landscape. The analysis found that the BRI was represented in a mostly positive light through both depictions of what it did and what it was. In addition, it was found that the BRI was often represented as a temporal and spatial context for the events of the news articles. These representations were given weight and significance through representing them as the reported speech of other individuals. In comparing the representations of the BRI in 2017 and 2019, it was found that the representations were broadly speaking familiar and had thus not been affected by the changes in the BRI’s image internationally between the Belt and Road Forums.
Keywords: Belt and Road Initiative, Belt and Road Forums for International Cooperation, China Daily, Transitivity, Systemic Functional Grammar